Respuesta :

Answer:

The answer to your question is (-1, 6)

Step-by-step explanation:

Data

                       7x - y = -13               Equation l

                      -3x - y = -3                Equation ll

-Solve equation l for y

                       y = 7x + 13                Equation lll

-Substitute equation lll in equation ll

                      -3x - (7x + 13) = -3

-Solve for x

                     -3x - 7x - 13 = -3

                     -10x = 13 - 3

                     -10x = 10

                          x = 10/-10

                          x = -1

-Substitute x in equation lll

                        y = 7(-1) + 13

                        y = -7 + 13

                        y = 6

ACCESS MORE